Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Kepuasan Pelanggan di Alfamidi Tinambung Kabupaten Polewali Mandar - Indah Sari; Erwin Erwin; Rahmat Ghazali (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of service quality and product quality on customer satisfaction at Alfamidi Tinambung, Polewali Mandar Regency. This study uses a quantitative approach with a causal-associative design. A sample of 100 respondents was determined using the Lemeshow formula with a purposive sampling technique. Data were collected through a 1–5 Likert scale questionnaire and analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that partially, service quality (t-count = 5.700 > t-table = 1.984; sig. = 0.000) and product quality (t-count = 4.576 > t-table = 1.984; sig. = 0.000) have a positive and significant effect on customer satisfaction. Simultaneously, both variables also have a significant effect (F-count = 79.456 > F-table = 3.09; sig. = 0.000) with a contribution of 62.3% (R Square = 0.623). Thus, all three hypotheses are accepted. This study recommends improving employee responsiveness and product availability management.